The Influence of Competence and Transformational Leadership on Employee Performance with Performance Motivation as A Mediating Variable in A State-Owned Enterprise Company (BUMN) Managing Water Resources - Yanti Ariani Sumarlin; Sunardi Sembiring Brahmana (Dinasti International Journal of Education Management And Social Science, 2025)
This study aims to examine the effect of competence and transformational leadership on employee performance, as well as the role of work motivation as a mediating variable, in the context of a state-owned company managing water resources, namely Perum Jasa Tirta II. The background of this research is the stagnation of employee performance that occurs despite policy changes and increasing demands for professionalism. The research method used is a quantitative approach with descriptive and verification designs, using data from 222 respondents analyzed through Partial Least Squares-based Structural Equation Modeling. The results showed that competence has a positive and significant effect on work motivation and employee performance, and work motivation is able to mediate the relationship between competence and performance. Meanwhile, transformational leadership only has a weak effect on performance and is insignificant on work motivation, and does not have a significant indirect effect on performance through motivation. In conclusion, competency development is more effective than the transformational leadership approach in improving employee performance in BUMN managing water resources.